Reflection about the criminalization of illicit enrichment in Brazil: an analysis of the constitutional legitimacy and criminal dogmatic of the law project 4850/2016 (2018)
This article aims to critically aboard the criminalization of illicit enrichment in Brazil, taking as a starting point the typical description proposed in the Law proyect 4850/2016, currently in legislative process, and subjecting it to constitutional tri